Identification and Prioritization of Indicators for the Annual Performance Evaluation of the President - Sotoodeh, Soroosh; Pourezzat, Aliasghar; Fayyazi, Marjan; Yaghoubi, NourMohammad; Mahbanooei, Bahareh (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: The objective of this study is to design and evaluate an annual performance evaluation model for the presidentMethodology: The study employs a Delphi research process consisting of three rounds to reach a consensus among expert panel members on the relevant performance indicators. Structural Equation Modeling (SEM) is used to validate the measurement model, and confirmatory factor analysis (CFA) is conducted to assess the reliability and validity of the model.Findings: The Cronbach's alpha coefficient and composite reliability for all constructs in the model exceed 0.7, indicating good and acceptable reliability for the measurement instruments. This implies that the various constructs of the model were measured consistently and accurately, and the resulting data can be reliably used to analyze and interpret the President’s performance. These results collectively show that the annual performance evaluation model for the President is statistically valid and can serve as an effective tool for performance analysis.Conclusion: Overall, the findings of this evaluation suggest that higher priority was given to indicators that refer to tangible and measurable outcomes and impacts of the President's performance. In contrast, indicators related to individual competencies and external and intervening factors ranked lower. This pattern may indicate a tendency toward evaluations that focus more on objective and observable results than on more relative or indirect assessments.